ГЕНЕТИЧНИЙ ПОЛІМОРФІЗМ ГАПЛОТИПУ RAD51-UTR ТА СХИЛЬНІСТЬ ДО РАКУ МОЛОЧНОЇ ЗАЛОЗИ У ЖІНОК З ЙОРДАНСЬКОЇ ПОПУЛЯЦІЇ - Al Zoubi, M.S.; AL-Eitan, L.N.; Rababa’h, D.M.; Al-Batayneh, K.; Farzand, R.; Quinn, G.A.; Tambuwala, M.M.; Bakshi, H.A. (PH Akademperiodyka, 2023)
Summary. Background: Genetic predisposition to breast cancer (BC) has been extensively explored to achieve an enhanced understanding of the biology of BC. Targeting candidate genes to screen different genetic variants such as RAD51 gene that plays a critical role in DNA repair pathways including the double-strand break repair system is an important task. Aim: To study several single nucleotide polymorphisms (SNPs) within RAD51-UTR gene and to find their relationship with BC risk and prognosis among Jordanian females. Materials and Methods: In this case-control study, DNA sequencing technique was used to screen SNPs within the untranslated region (UTR) of RAD51 in 206 cases and 185 controls and the resulting data were statistically analyzed using different types of genetic analyses. Patients’ clinical and pathological features were obtained from their medical records to perform genotype-phenotype association analysis. Results: Our findings show a significant association between both SNPs rs528590644, rs1801320 and BC risk (p = 0.016). We estimated the correlation between many of BC prognostic factors and BC risk, and we found an association between rs1801321 and age at first menstruation (p = 0.032) in addition to a strong correlation between age at BC diagnosis and rs1801320 (p = 0.008). Conclusion: RAD51-UTR polymorphisms may be involved in BC development and progression.